Exploring the Impact of Academic Self-Concept on Learning Engagement: The Mediating Role of Teacher Expectations - Wang, Zhen; Pan, Xiaoquan (Social Education Research, 2025)
Learning engagement pertains to a psychological state in which individuals uphold a sustained positive attitude, emotions, and cognitive processes while engaging in learning, research, or work activities. Academic self-concept, being a crucial factor that influences students' learning outcomes, has attracted extensive attention from scholars in the academic field. This research, with college students as the research participants, aims to explore the impact of academic self-concept on learning engagement and to examine the mediating role of teacher expectations within these relationships. A total of 280 college students participated in the questionnaire survey in this study, which involved the variables of their academic self-concept, learning engagement, and teacher expectations. Correlation analysis and mediation effect tests demonstrated a clear correlation between students' learning engagement and their academic self-concept, and teacher expectations served as a crucial mediator in the intricate relationship between academic self-concept and learning engagement. Specifically, students with a higher level of academic self-concept exhibited higher learning engagement. This study not only confirmed the importance of nurturing a positive academic self-concept among college students but also highlighted the significant impact that teachers can have on shaping students' academic self-concept. By recognizing and addressing the role of teacher expectations as a mediating factor, educators can take proactive steps to foster an environment that promotes academic self-concept and enhances learning engagement.